2010
DOI: 10.1016/j.bcp.2009.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel 12-nucleotide insertion polymorphism in the promoter region of ADRA2B: Full linkage with the 9-nucleotide deletion in the coding region and influence on transcriptional activity

Abstract: , et al.. Identification of a novel 12-nucleotide insertion polymorphism in the promoter region of ADRA2B: full linkage with the 9-nucleotide deletion in the coding region and influence on transcriptional activity. Biochemical Pharmacology, Elsevier, 2009, 79 (3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…The present case-control association study indicates that ADRA2B -4825 indel polymorphism is not associated with migraine, which is consistent with a previous report [7] . Since the -4825 indel polymorphism is in complete linkage with the indel polymorphism at position +901 and a G/C substitution at position -98 [9] , combined with previously reported data for female migraine subjects [8] , our findings do not support a major role of the polymorphisms within adrenergic receptor systems in migraine pathology.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The present case-control association study indicates that ADRA2B -4825 indel polymorphism is not associated with migraine, which is consistent with a previous report [7] . Since the -4825 indel polymorphism is in complete linkage with the indel polymorphism at position +901 and a G/C substitution at position -98 [9] , combined with previously reported data for female migraine subjects [8] , our findings do not support a major role of the polymorphisms within adrenergic receptor systems in migraine pathology.…”
Section: Discussioncontrasting
confidence: 63%
“…More recently, a population study has identified a novel 12-nucleotide (GGGACGGCCCTG) insertion/deletion (indel) polymorphism at position -4825 relative to the start codon in the far upstream region of the ADRA2B promoter (-4825 indel). Besides, this indel polymorphism is shown to be common and in complete linkage with the deletion polymorphism at position +901 and a G/C substitution at position -98 [9] . The present study was aimed to investigate whether the 12-bp indel polymorphism is associated with migraine in Chinese Han population.…”
Section: Introductionmentioning
confidence: 95%
“…The impact of a 2B AR Del301-303 observed varies based on a number of factors, particularly the ethnic makeup of the sample population. As well, given that the Del301-303 polymorphism is in linkage with other a 2B AR polymorphisms in certain populations (Cayla et al, 2004;Etzel et al, 2005;Crassous et al, 2010), it is possible that there are complex effects of the a 2B AR genotype. As an example, the Del301-303 polymorphism may result in enhanced receptor signaling while a noncoding polymorphism such as the 5 0 -UTR deletion beginning at position -4825 may lead to decreased receptor expression.…”
Section: B Hypertensionmentioning
confidence: 96%
“…Interestingly, these five polymorphisms listed above have been found to be in linkage with each other, especially in the Caucasian population (Cayla et al, 2004;Etzel et al, 2005;Crassous et al, 2010). At the molecular level, the noncoding region polymorphisms may have effects on transcriptional activity at the a 2B AR gene, thereby affecting receptor expression levels (Cayla et al, 2004).…”
Section: B a 2b Armentioning
confidence: 97%
See 1 more Smart Citation